Atlas of human anatomy - Netter, Frank H. (Frank Henry), 1906-1991 (Saunders/Elsevier, 2014)
This book offers unsurpassed depictions of the human body in clear, brilliant detail, all from a clinician's perspective. With its emphasis on anatomic relationships and clinically relevant views, this work provides a coherent, lasting visual vocabulary for understanding anatomy and how it applies to medicine today.